Reactive Oxygen Species (ROS) Generation Is Indispensable for Haustorium Formation of the Root Parasitic Plant Striga hermonthica - Wada, Syogo; Cui, Songkui; Yoshida, Satoko (Frontiers in Plant Science, 2019)
The parasitic witchweed Striga hermonthica causes devastating damage to crops in sub-Saharan Africa, yet the mechanism of its parasitism is not well understood. Parasitic plants form a special organ called a haustorium to obtain water and nutrients from host plants. The haustorium is induced by host-derived small molecules, collectively named haustorium-inducing factors (HIFs). The most active HIF known to date is 2,6-dimethoxy-p-benzoquinone (DMBQ), originally isolated from sorghum root extracts. It has been suggested that DMBQ is produced by oxidation of its precursor, syringic acid, and that reactive oxygen species (ROS) and peroxidases are involved in the process. However, the roles of ROS in haustorium formation after HIF recognition remain to be elucidated. Here, we investigated the effects of various inhibitors of ROS and ROS-regulating enzymes on haustorium formation in S. hermonthica. Inhibitors of NADPH oxidases and peroxidases inhibited haustorium formation during treatment with DMBQ, syringic acid and host root extracts, suggesting that ROS production and/or regulation via NADPH oxidases and peroxidases are essential for haustorium formation. We observed hydrogen peroxide accumulation in the haustorium upon treatment with various HIFs. Our results suggest that ROS and ROS-regulating enzymes are indispensable in downstream signaling of HIFs for haustorium formation.